2012
DOI: 10.1002/chin.201214259
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Oxidation of Chemical Compounds: Kinetics and Mechanistic Approach

Abstract: Review: 101 refs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Chemical kinetics is concerned with understanding the rates of chemical reaction, the speed at which chemical species can transform into new substances by breaking and reforming the chemical bonds (Srgoura et al, 2011). It can reasonably guide us to control the reaction conditions and improve the reaction rate, to increase the production of chemical products, and also guide us to learn how to suppress or slow down the reaction rate of side reactions to reduce the consumption of raw materials (Zhang et al, 2020;Keith, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Chemical kinetics is concerned with understanding the rates of chemical reaction, the speed at which chemical species can transform into new substances by breaking and reforming the chemical bonds (Srgoura et al, 2011). It can reasonably guide us to control the reaction conditions and improve the reaction rate, to increase the production of chemical products, and also guide us to learn how to suppress or slow down the reaction rate of side reactions to reduce the consumption of raw materials (Zhang et al, 2020;Keith, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Veeraiah, M.K et al, 22 29 , have shown the oxidation of drugs by using CAT as oxidising agents in various methods. Literature shows oxidation of methyl vinyl ketone and isopropyl methyl ketone, ketoglutaric acids, formic acids, substituted transcinnamic acids, methionine, substituted and unsubstituted imidazole and benzimidazoles done by using CAT as an oxidising agent 30 .…”
mentioning
confidence: 99%